Extraction, characterisation and application of betalains from cactus pear, beetroot and amaranth - Sigwela, Vuyisa Ntombiyolwazi (University of the Free State, 2020)
According to Europe, Middle East, and Africa (EMEA) Mintel Food and Drink Trends in 2018, consumers require explicit disclosure on food and drink labels. The requirements go hand in hand with the preference for nutritionally-dense foods that are pleasing to the eye and prepared under safe conditions (Gengatharan et al., 2015; Martins et al., 2016). The preference for explicit disclosure includes information on how, as well as where, products are grown and produced, and could result in interactive, reliable relationships between customers and the food industry. The food industry is, therefore, presented with an opportunity to conduct research on various colourants that are available in the market, the countries that consume them, their healthful and detrimental effects, as well as which ones can be used in the food industry going forward. This chapter gives an understanding of consumer perceptions, some of the different colourants that exist, their characterisation, as well as application in foods. It further shows the need for the industry to shift to natural colourants by drawing particular attention to the benefits of natural plant pigments, primarily betalains.
Dissertation (M.Sc.Home Ec. (Consumer Science))--University of the Free State, 2020
Keywords: Amaranth; Antioxidant capacity; Antioxidants; Beet (beetroot) red; Beetroot; Betacyanins; Betalains; Betaxanthins; Cactus Pear; Colourants; Colouring Foods; Natural colourants; Opuntia ficus-indica; Opuntia robusta; Pigments; Product development